2018
DOI: 10.1038/s41467-018-04019-9
|View full text |Cite
|
Sign up to set email alerts
|

Methylated DNMT1 and E2F1 are targeted for proteolysis by L3MBTL3 and CRL4DCAF5 ubiquitin ligase

Abstract: Many non-histone proteins are lysine methylated and a novel function of this modification is to trigger the proteolysis of methylated proteins. Here, we report that the methylated lysine 142 of DNMT1, a major DNA methyltransferase that preserves epigenetic inheritance of DNA methylation patterns during DNA replication, is demethylated by LSD1. A novel methyl-binding protein, L3MBTL3, binds the K142-methylated DNMT1 and recruits a novel CRL4DCAF5 ubiquitin ligase to degrade DNMT1. Both LSD1 and PHF20L1 act prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
178
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(184 citation statements)
references
References 58 publications
(132 reference statements)
5
178
1
Order By: Relevance
“…Our analysis also revealed the presence of peptides from DDB1 and DCAF5, components of the CRL4 DCAF5 ubiquitin E3 ligase complexes ( Fig. 1B and Table 1) (29). Our independent immunoprecipitation and Western blotting analyses in mouse ES cells confirmed that the components of the CRL4 DCAF5 , such as CUL4A or CUL4B, DDB1, and DCAF5, are associated with endogenous SOX2 protein ( Fig.…”
Section: Methylated Sox2 Is Regulated By L3mbtl3 and Crl4 Dcaf5supporting
confidence: 69%
See 4 more Smart Citations
“…Our analysis also revealed the presence of peptides from DDB1 and DCAF5, components of the CRL4 DCAF5 ubiquitin E3 ligase complexes ( Fig. 1B and Table 1) (29). Our independent immunoprecipitation and Western blotting analyses in mouse ES cells confirmed that the components of the CRL4 DCAF5 , such as CUL4A or CUL4B, DDB1, and DCAF5, are associated with endogenous SOX2 protein ( Fig.…”
Section: Methylated Sox2 Is Regulated By L3mbtl3 and Crl4 Dcaf5supporting
confidence: 69%
“…Mouse null mutation of L3MBTL3 causes late embryonic lethality (36). Our recent studies revealed that L3MBTL3 is critical in regulating the protein stability of DNMT1 when it is methylated by SET7 (29). L3MBTL3 is thus a good candidate for the methylated SOX2 proteolysis, although there are substantial differences between the Lys-42 methylation motif and the surrounding region in SOX2 and that of the methylated Lys-142 in DNMT1 ( Fig.…”
Section: Methylated Sox2 Is Regulated By L3mbtl3 and Crl4 Dcaf5mentioning
confidence: 97%
See 3 more Smart Citations